Mencari Model Tata Ibadah dalam Gereja Kristen Nazarene di Indonesia di Abad XXI - Bakhoh Jatmiko (SANCTUM DOMINE: JURNAL TEOLOGI, 2018)
Worship is one expression of a human as a spiritual being. Deep inside a person, there is always a spiritual awareness that makes the person have a need of spiritual relationship with the Creator. In the Church context, worship is conducted with many forms and elements. The number of denominations and liturgies often lead to both a confusion and longing for a formulation or guidance in shaping a liturgy. The style and concept of worship in the Nazarene Church in Indonesia needs an emphasise on its understanding related to the denomination’s history. The Nazarene Church has been in existence Indonesia for almost four decades and spread to many different places in Indonesia.